Light-operated composite phase change material catalyst as well as preparation method and application thereof
By using a photo-controlled composite phase change material catalyst and a halloysite/sodium alginate aerogel support material supported by metal M nanoparticles, combined with photothermal conversion to control hydrogen release, the problem of controlling hydrogen release during the hydrolysis of ammonia borane was solved, achieving efficient and stable hydrogen release control.
Patent Information
- Application Number
- CN202511479408.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-16
- Publication Date
- 2025-12-16
AI Technical Summary
Existing technologies are insufficient to effectively control the controlled release of hydrogen during the hydrolysis of ammonia borane, and the process of controlling hydrogen release is complex and requires the addition of other chemical reagents.
A photo-controlled composite phase change material catalyst is used. By encapsulating paraffin with a metal M/haloysite/sodium alginate composite phase change material, and using halloysite/sodium alginate aerogel supported by metal M nanoparticles as a support material, combined with photothermal conversion to control hydrogen release, the physical exposure and shielding of active sites are achieved.
It achieves precise control of hydrogen release, improves photothermal conversion efficiency, and possesses good mechanical and chemical stability, making it suitable for industrial production.
Smart Images

Figure CN121130879A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of phase change materials, in particular to a light-controlled composite phase change material catalyst and a preparation method and application thereof. BACKGROUND
[0002] With the continuous rapid development of human society, non-renewable fossil energy is increasingly exhausted. Developing green and sustainable new energy is the recognized future energy direction and strategic choice, aiming to address the energy problems caused by the exhaustion of fossil fuels and the environmental challenges caused by long-term industrial activities—especially the global warming problem. Hydrogen is considered an important carrier of future energy supply, and effective and safe storage and release of hydrogen is a prerequisite for future hydrogen economy. Ammonia borane hydrolysis to produce hydrogen is considered one of the most promising chemical hydrogen storage technologies due to its high hydrogen storage density of 19.6 wt%, environmentally friendly reaction path, and mild operating conditions.
[0003] Phase change materials, as heat storage materials, can undergo phase change processes at constant temperatures and absorb or release a large amount of latent heat, with high energy storage density, no pollution, etc., and are widely used in solar heat utilization, catalysis, building energy storage, etc. In the field of catalysis, phase change materials themselves do not have catalytic function, so it is necessary to couple with catalysts to prepare composite phase change materials. The close combination of catalysts and phase change materials can effectively and timely transfer the heat generated by the reaction. However, solid-liquid phase change materials inevitably leak during the phase change process. Aerogels with ultra-low density, ultra-high porosity, and large specific surface area have been widely used in the synthesis of shape-stable phase change materials, which can effectively solve the leakage problem during the phase change process. Controllable release of hydrogen during ammonia borane hydrolysis is of great significance to the practical application and effective use of hydrogen energy, however, this process is difficult to control. Currently, the release of hydrogen is mainly controlled by controlling the amount of ammonia borane solution or by the amount of catalyst. Although it can achieve the control of hydrogen release, the process of controlling the generation of hydrogen by ammonia borane in the liquid phase system is complex, and other chemical reagents need to be added.
[0004] Therefore, there is an urgent need for a light-controlled composite phase change material catalyst and a preparation method and application thereof to solve the above technical problems. SUMMARY
[0005] The present application aims to overcome the above technical problems and provide a light-controlled composite phase change material catalyst and a preparation method and application thereof.
[0006] To achieve the above-mentioned purpose, the present application is implemented according to the following technical solutions: A photo-controlled composite phase change material catalyst, wherein the photo-controlled composite phase change material catalyst is a metal M / haloite / sodium alginate composite phase change material encapsulating paraffin; the metal M / haloite / sodium alginate composite phase change material encapsulating paraffin uses halloysite / sodium alginate aerogel supported by metal M nanoparticles as a supporting material and encapsulates paraffin.
[0007] Preferably, the metal M is one of silver (Ag), cobalt (Co), and ruthenium (Ru).
[0008] More preferably, the metal M is silver (Ag).
[0009] The metal M / haloite / sodium alginate composite phase change material encapsulating paraffin is designated as PW@M / HNTA.
[0010] This invention also includes a method for preparing a light-controlled composite phase change material catalyst, comprising the following steps: S1, Halloysite nanotubes are added to hydrochloric acid solution and stirred. After stirring, they are washed and dried to obtain acid-treated halloysite nanotubes. S2, acid-treated halloysite nanotubes were added to sodium alginate solution and stirred, glutaraldehyde solution was added and stirred, and then freeze-dried to obtain halloysite / sodium alginate aerogel. S3, Halloysite / sodium alginate aerogel is immersed in a salt solution of metal M, sodium borohydride is added after impregnation, and then freeze-drying is performed to obtain metal M / haloysite / sodium alginate aerogel. S4. The metal M / haloysite / sodium alginate aerogel is immersed in molten paraffin wax to encapsulate the paraffin wax, thereby obtaining a metal M / haloysite / sodium alginate composite phase change material encapsulated in paraffin wax.
[0011] Preferably, in step S1, the stirring time is 3 hours, the stirring temperature is 80°C, and the concentration of the hydrochloric acid solution is 4 mol / L.
[0012] Preferably, in step S2, the mass fraction of the sodium alginate solution is 2%; the mass ratio of the acid-treated halloysite nanotubes to the sodium alginate in the sodium alginate solution is 5:1; the mass-volume ratio of the acid-treated halloysite nanotubes to the glutaraldehyde solution is 1:1000, with the comparison unit being g: μL; and the mass fraction of glutaraldehyde in the glutaraldehyde solution is 25%.
[0013] Preferably, in step S3, the concentration of the salt solution of metal M is 3 g / L; the mass-to-volume ratio of the acid-treated halloysite nanotubes to the salt solution of metal M is 1:(2-39), with the unit of comparison being g:mL; and the mass ratio of the acid-treated halloysite nanotubes to sodium borohydride is 25:1.
[0014] Preferably, the salt solution of metal M is one of silver nitrate solution, anhydrous ruthenium chloride solution, and cobalt chloride hexahydrate solution.
[0015] Preferably, the loading of metal M is 1%-5% of the mass of metal M / haloysite / sodium alginate aerogel.
[0016] Preferably, in step S5, the encapsulation process of paraffin is automatic encapsulation, and the encapsulation amount of paraffin in the metal M / haloite / sodium alginate composite phase change material encapsulating paraffin is 65%-85%.
[0017] Specifically, the preparation method of the light-controlled composite phase change material catalyst includes the following steps: S1, Halloysite nanotubes were added to a 4 M hydrochloric acid solution and stirred in an oil bath at 80 °C for 3 h; after stirring, they were washed with deionized water to neutralize and then dried for 24 h to obtain acid-treated halloysite nanotubes. S2, sodium alginate solid was added to deionized water and stirred until dissolved to obtain sodium alginate solution; acid-treated halloysite nanotubes were added to sodium alginate solution and stirred for 12 h, then 25 wt% glutaraldehyde solution was added and stirred for another 12 h, and then freeze-dried to obtain halloysite / sodium alginate aerogel. S3, the halloysite / sodium alginate aerogel was immersed in the salt solution of metal M for 12 h, then sodium borohydride was added for reduction, and the resulting sample was freeze-dried to obtain metal M / haloysite / sodium alginate aerogel. S4. Paraffin wax is placed in a beaker and melted in a vacuum drying oven at 80 ℃. Then, metal M / haloite / sodium alginate aerogel is placed inside. The metal M / haloite / sodium alginate aerogel has an interconnected three-dimensional porous structure. Due to capillary forces and surface tension, the metal M / haloite / sodium alginate aerogel with an interconnected three-dimensional porous structure automatically completes the encapsulation of paraffin wax under vacuum, thus obtaining a metal M / haloite / sodium alginate composite phase change material encapsulating paraffin wax.
[0018] The present invention also includes the application of light-controlled composite phase change material catalysts in the hydrolysis of ammonia borane to produce hydrogen.
[0019] The application process is as follows: the light-controlled composite phase change material catalyst PW@M / HNTA is placed in a container, and an aqueous solution of ammonia borane is injected into the container. The hydrogen production from the hydrolysis of ammonia borane is controlled by turning the light source on and off. When the light source is turned off, the hydrogen production from the hydrolysis of ammonia borane is terminated.
[0020] The photo-controlled composite phase change material catalyst of the present invention has a three-dimensional network structure formed by cross-linking aerogel, which can encapsulate paraffin up to 86%. The loaded metal M nanoparticles can form a photothermal layer. The melting and solidification of paraffin in the composite phase change material can be controlled by turning the light source on and off, thereby achieving physical exposure and shielding of active sites, thus precisely starting and stopping the catalytic reaction, and realizing the complete start and stop of the reaction.
[0021] This invention discloses a composite phase change material encapsulating paraffin (PW) with halloysite / sodium alginate aerogel (HNTA) supporting metal M nanoparticles as the support material. The material uses oriented, layered porous aerogel (HNTA) as its core framework. The dense photothermal layer formed by the metal M nanoparticles endows the composite material with high light absorption capacity, enabling rapid heating to the melting point of PW under simulated sunlight. The dynamic coupling between the catalytic activity of the metal M nanoparticles and the phase change behavior of paraffin enables light-controlled on-demand hydrogen release: light irradiation triggers paraffin melting, exposing the active sites of metal M to catalyze the hydrolysis of ammonia borane to produce hydrogen; under no-light conditions, the paraffin solidifies, shielding the active sites of metal M and precisely blocking the reaction pathway. This integrated "energy storage-thermal conduction-catalysis" design concept not only establishes a new paradigm for the synergistic optimization of solar photothermal conversion and chemical energy storage but also lays the material foundation for advanced applications such as intelligent thermal management systems and the regulation of catalytic reactions.
[0022] This invention controls the melting and solidification of paraffin in a photo-controlled composite phase change material catalyst by turning the light source on and off, achieving physical exposure and shielding of active sites. This allows for precise activation and deactivation of the catalytic reaction, enabling complete start-up and cessation of the reaction. Specifically, under light irradiation, photothermal conversion triggers the melting of paraffin, exposing the active metal M catalytic sites to an aqueous environment. This structural reconstruction allows water molecules and ammonia borane to interact simultaneously with the activated metal M surface, promoting the hydrolysis of ammonia borane to produce hydrogen. When the light is off, the solidified paraffin re-encapsulates the metal M sites, preventing the reaction from proceeding.
[0023] The photo-controlled composite phase change material catalyst of the present invention is a novel catalytic system that combines complete reaction blocking and efficient thermal management.
[0024] Mechanism of action: The metal M / haloysite / sodium alginate composite phase change material encapsulated with paraffin prepared in this invention uses halloysite / sodium alginate aerogel supported by metal M nanoparticles as the supporting material. Under light irradiation, photothermal conversion triggers the melting of paraffin in the composite phase change material, exposing the active metal M catalytic sites to an aqueous environment. This structural reconstruction allows water molecules and ammonia borane to interact simultaneously with the activated metal M surface, promoting the hydrolysis of ammonia borane to produce hydrogen. When the light stops, the paraffin solidifies and re-encapsulates the metal M sites, preventing the reaction from proceeding.
[0025] Beneficial effects: In terms of material preparation, this invention utilizes halloysite nanotubes to prepare a metal M / haloysite / sodium alginate composite phase change material encapsulating paraffin. The aerogel (metal M / haloysite / sodium alginate aerogel) in this invention has a large encapsulation capacity for paraffin; approximately 0.5 g of aerogel can encapsulate approximately 3.8 g of paraffin, with an encapsulation rate of up to 86%. Furthermore, after multiple endothermic and exothermic cycles, this phase change material still maintains good mechanical and chemical stability. In terms of material application, this invention utilizes the loading of metal M nanoparticles to achieve a photothermal conversion efficiency of >90% for the composite phase change material. Simultaneously, it can control the melting and solidification of paraffin through light irradiation, achieving physical exposure and shielding of the active sites of metal M, thereby precisely starting and stopping the catalytic reaction, possessing the capability for practical industrial production applications. Attached Figure Description
[0026] Figure 1 The scanning electron microscope (SEM) shows the silver / halothite / sodium alginate aerogel obtained in step 7 of Example 1 of the present invention. Figure 2 This is a graph showing the mass change of the silver / halolite / sodium alginate aerogel prepared in Example 1 of the present invention before and after encapsulating paraffin. Figure 3 Comparison of light absorption performance of pure paraffin, silver / halolite / sodium alginate composite phase change material encapsulating paraffin in Example 1 of this invention, and halloysite / sodium alginate composite phase change material encapsulating paraffin in Comparative Example 1. Figure 4 Comparison of the hydrogen production performance of silver / halolite / sodium alginate composite phase change materials encapsulated in paraffin prepared in Examples 1, 2, and 3 of this invention under light-on / off conditions; Figure 5 The graph shows a comparison of the hydrogen production performance of halloysite / sodium alginate composite phase change materials with different metal loads on encapsulated paraffin prepared in Examples 1, 4, and 5 of this invention under light-on / off conditions. Detailed Implementation
[0027] The present invention will be further described below with reference to specific embodiments. The illustrative embodiments and descriptions herein are used to explain the present invention, but are not intended to limit the present invention.
[0028] There are no particular restrictions on the source of any raw materials used in this invention; they can be purchased from the market or prepared using conventional methods known to those skilled in the art.
[0029] There are no particular restrictions on the purity of any of the raw materials used in this invention; however, it is preferred to use materials with conventional purity levels used in the field.
[0030] All processes in this invention are referred to by abbreviations that are common abbreviations in the field. Each abbreviation is clear and specific in its relevant application area, and those skilled in the art can understand its conventional process steps based on the abbreviation.
[0031] Example 1: A method for preparing a light-controlled composite phase change material catalyst includes the following steps: 1) Add the collected halloysite nanotubes to 4 M hydrochloric acid and stir in an oil bath at 80 °C for 3 h; 2) The above sample was washed with deionized water until neutral and then dried for 24 h to obtain acid-treated halloysite nanotubes; 3) Take 200 mg of sodium alginate solid and add it to 10 mL of deionized water. Stir until it dissolves to obtain sodium alginate solution. 4) Take 1 g of the acid-treated halloysite nanotubes obtained in step 2) and add them to the sodium alginate solution (2 wt%) in step 3). After stirring for 12 h, add 1000 μL of 25% glutaraldehyde solution and stir for another 12 h. Pour the mixture into a mold and freeze it in a refrigerator for 2 h. Take it out and put it into a freeze dryer for 48 h to obtain halloysite / sodium alginate aerogel with an interconnected three-dimensional porous structure. 5) Dissolve 0.3 g of silver nitrate in 100 mL of water to obtain a silver nitrate solution (3 g / L). 6) Immerse the aerogel obtained in step 4) in 13 mL of silver nitrate solution (3 g / L) for 12 h, then add 40 mg of sodium borohydride to reduce it and take out the sample, and rinse it three times with deionized water. 7) Place the sample obtained in step 6) in a freezer for 2 hours, then place it in a freeze dryer for 18 hours to obtain silver / halolite / sodium alginate aerogel. 8) Place the paraffin wax in a beaker and heat it to melt in a vacuum drying oven at 80 ℃. Then, place the silver / halolite / sodium alginate aerogel with an interconnected three-dimensional porous structure into the melted paraffin wax. Due to capillary force and surface tension, the aerogel with an interconnected three-dimensional porous structure automatically completes the encapsulation of the paraffin wax under vacuum, thus obtaining the silver / halolite / sodium alginate composite phase change material encapsulated in paraffin wax, denoted as 5%PW@Ag / HNTA.
[0032] Example 2: A method for preparing a light-controlled composite phase change material catalyst includes the following steps: 1) Add the collected halloysite nanotubes to 4 M hydrochloric acid and stir in an oil bath at 80 °C for 3 h; 2) The above sample was washed with deionized water until neutral and then dried for 24 h to obtain acid-treated halloysite nanotubes; 3) Take 200 mg of sodium alginate solid and add it to 10 mL of deionized water. Stir until it dissolves to obtain sodium alginate solution. 4) Take 1 g of the acid-treated halloysite nanotubes obtained in step 2) and add them to the sodium alginate solution (2 wt%) in step 3). After stirring for 12 h, add 1000 μL of 25% glutaraldehyde solution and stir for another 12 h. Pour the mixture into a mold and freeze it in a refrigerator for 2 h. Take it out and put it into a freeze dryer for 48 h to obtain halloysite / sodium alginate aerogel with an interconnected three-dimensional porous structure. 5) Dissolve 0.3 g of silver nitrate in 100 mL of water to obtain a silver nitrate solution (3 g / L). 6) Immerse the aerogel obtained in step 4) in 7.8 mL of silver nitrate solution (3 g / L) for 12 h, then add 40 mg of sodium borohydride to reduce it and take out the sample, and rinse it three times with deionized water. 7) Place the sample obtained in step 6) in a freezer for 2 hours, then place it in a freeze dryer for 18 hours to obtain silver / halolite / sodium alginate aerogel. 8) Place the paraffin wax in a beaker and heat it to melt in a vacuum drying oven at 80 ℃. Then, place the silver / halolite / sodium alginate aerogel with an interconnected three-dimensional porous structure into the melted paraffin wax. Due to capillary force and surface tension, the aerogel with an interconnected three-dimensional porous structure automatically completes the encapsulation of the paraffin wax under vacuum, thus obtaining the silver / halolite / sodium alginate composite phase change material encapsulating paraffin wax, denoted as 3%PW@Ag / HNTA.
[0033] Example 3: A method for preparing a light-controlled composite phase change material catalyst includes the following steps: 1) Add the collected halloysite nanotubes to 4 M hydrochloric acid and stir in an oil bath at 80 °C for 3 h; 2) The above sample was washed with deionized water until neutral and then dried for 24 h to obtain acid-treated halloysite nanotubes; 3) Take 200 mg of sodium alginate solid and add it to 10 mL of deionized water. Stir until it dissolves to obtain sodium alginate solution. 4) Take 1 g of the acid-treated halloysite nanotubes obtained in step 2) and add them to the sodium alginate solution (2 wt%) in step 3). After stirring for 12 h, add 1000 μL of 25% glutaraldehyde solution and stir for another 12 h. Pour the mixture into a mold and freeze it in a refrigerator for 2 h. Take it out and put it into a freeze dryer for 48 h to obtain halloysite / sodium alginate aerogel with an interconnected three-dimensional porous structure. 5) Dissolve 0.3 g of silver nitrate in 100 mL of water to obtain a silver nitrate solution (3 g / L). 6) Immerse the aerogel obtained in step 4) in 2.6 mL of silver nitrate solution (3 g / L) for 12 h, then add 40 mg of sodium borohydride to reduce it and take out the sample, and rinse it three times with deionized water. 7) Place the sample obtained in step 6) in a freezer for 2 hours, then place it in a freeze dryer for 18 hours to obtain silver / halolite / sodium alginate aerogel. 8) Place the paraffin wax in a beaker and heat it to melt in a vacuum drying oven at 80 ℃. Then, place the silver / halolite / sodium alginate aerogel with an interconnected three-dimensional porous structure into the melted paraffin wax. Due to capillary force and surface tension, the aerogel with an interconnected three-dimensional porous structure automatically completes the encapsulation of the paraffin wax under vacuum, thus obtaining the silver / halolite / sodium alginate composite phase change material encapsulated in paraffin wax, denoted as 1%PW@Ag / HNTA.
[0034] Example 4: A method for preparing a light-controlled composite phase change material catalyst includes the following steps: 1) Add the collected halloysite nanotubes to 4 M hydrochloric acid and stir in an oil bath at 80 °C for 3 h; 2) The above sample was washed with deionized water until neutral and then dried for 24 h to obtain acid-treated halloysite nanotubes; 3) Take 200 mg of sodium alginate solid and add it to 10 mL of deionized water. Stir until it dissolves to obtain sodium alginate solution. 4) Take 1 g of the acid-treated halloysite nanotubes obtained in step 2) and add them to the sodium alginate solution (2 wt%) in step 3). After stirring for 12 h, add 1000 μL of 25% glutaraldehyde solution and stir for another 12 h. Pour the mixture into a mold and freeze it in a refrigerator for 2 h. Take it out and put it into a freeze dryer for 48 h to obtain halloysite / sodium alginate aerogel with an interconnected three-dimensional porous structure. 5) Dissolve 0.3 g of anhydrous ruthenium trichloride (RuCl3) in 100 mL of water to obtain a ruthenium trichloride solution (3 g / L). 6) Immerse the aerogel obtained in step 4) in 24 mL of ruthenium trichloride solution (3 g / L) for 12 h, then add 40 mg of sodium borohydride to reduce it, take out the sample, and rinse it three times with deionized water. 7) Place the sample obtained in step 6) in a freezer for 2 hours, then place it in a freeze dryer for 18 hours to obtain ruthenium / halolite / sodium alginate aerogel. 8) Place the paraffin wax in a beaker and heat it to melt in a vacuum drying oven at 80 ℃. Then, place the ruthenium / halolite / sodium alginate aerogel with an interconnected three-dimensional porous structure into the melted paraffin wax. Due to capillary force and surface tension, the aerogel with an interconnected three-dimensional porous structure automatically completes the encapsulation of the paraffin wax under vacuum, thus obtaining the ruthenium / halolite / sodium alginate composite phase change material encapsulated in paraffin wax, denoted as 5%PW@Ru / HNTA.
[0035] Example 5: A method for preparing a light-controlled composite phase change material catalyst includes the following steps: 1) Add the collected halloysite nanotubes to 4 M hydrochloric acid and stir in an oil bath at 80 °C for 3 h; 2) The above sample was washed with deionized water until neutral and then dried for 24 h to obtain acid-treated halloysite nanotubes; 3) Take 200 mg of sodium alginate solid and add it to 10 mL of deionized water. Stir until it dissolves to obtain sodium alginate solution. 4) Take 1 g of the acid-treated halloysite nanotubes obtained in step 2) and add them to the sodium alginate solution (2 wt%) in step 3). After stirring for 12 h, add 1000 μL of 25% glutaraldehyde solution and stir for another 12 h. Pour the mixture into a mold and freeze it in a refrigerator for 2 h. Take it out and put it into a freeze dryer for 48 h to obtain halloysite / sodium alginate aerogel with an interconnected three-dimensional porous structure. 5) Dissolve 0.3 g of cobalt chloride hexahydrate (CoCl2·6H2O) in 100 mL of water to obtain a cobalt chloride hexahydrate solution (3 g / L). 6) Immerse the aerogel obtained in step 4) in 33 mL of cobalt dichloride hexahydrate solution (3 g / L) for 12 h, then add 40 mg of sodium borohydride to reduce it and take out the sample, and rinse it three times with deionized water. 7) Place the sample obtained in step 6) in a freezer for 2 hours, then place it in a freeze dryer for 18 hours to obtain cobalt / halolite / sodium alginate aerogel. 8) Place the paraffin wax in a beaker and heat it to melt in a vacuum drying oven at 80 ℃. Then, place the cobalt / halolite / sodium alginate aerogel with an interconnected three-dimensional porous structure into the melted paraffin wax. Due to capillary force and surface tension, the aerogel with an interconnected three-dimensional porous structure automatically completes the encapsulation of the paraffin wax under vacuum, thus obtaining the cobalt / halolite / sodium alginate composite phase change material encapsulating paraffin wax, denoted as 5%PW@Co / HNTA.
[0036] Comparative Example 1: 1) Add the collected halloysite nanotubes to 4 M hydrochloric acid and stir in an oil bath at 80 °C for 3 h; 2) The above sample was washed with deionized water until neutral and then dried for 24 h to obtain acid-treated halloysite nanotubes; 3) Take 200 mg of sodium alginate solid and add it to 10 mL of deionized water. Stir until it dissolves to obtain sodium alginate solution. 4) Take 1 g of the acid-treated halloysite nanotubes obtained in step 2) and add them to the sodium alginate solution (2 wt%) in step 3). After stirring for 12 h, add 1000 μL of 25% glutaraldehyde solution and stir for another 12 h. Pour the mixture into a mold and freeze it in a refrigerator for 2 h. Take it out and put it into a freeze dryer for 48 h to obtain halloysite / sodium alginate aerogel with an interconnected three-dimensional porous structure.
[0037] 5) Place the paraffin wax in a beaker and heat it to melt in a vacuum drying oven at 80 ℃. Place the halloysite / sodium alginate aerogel with an interconnected three-dimensional porous structure into the melted paraffin wax. Due to capillary force and surface tension, the aerogel with an interconnected three-dimensional porous structure automatically completes the encapsulation of the paraffin wax under vacuum, thus obtaining the halloysite / sodium alginate composite phase change material encapsulated with paraffin wax, denoted as PW@HNTA.
[0038] like Figure 1 The image shows a scanning electron microscope (SEM) image of the silver / halolite / sodium alginate aerogel obtained in step 7 of Example 1 of this invention; as can be seen from the image, the silver / halolite / sodium alginate aerogel is an aerogel with an interconnected three-dimensional porous structure.
[0039] like Figure 2 The figure shown is a graph illustrating the mass change of the silver / halolite / sodium alginate aerogel prepared in Example 1 of this invention before and after encapsulating paraffin. Figure 2 Figure a shows the mass of the silver / halolite / sodium alginate aerogel obtained in step 7, which is 0.5335 g; Figure 2 Figure b shows the silver / halolite / sodium alginate composite phase change material encapsulated with paraffin obtained in step 8, i.e., the silver / halolite / sodium alginate aerogel encapsulated with paraffin, with a mass of 3.8699 g.
[0040] like Figure 3The figure shows a comparison of the light absorption performance of pure paraffin, the silver / halothite / sodium alginate composite phase change material encapsulated in paraffin of Example 1 of this invention, and the halloysite / sodium alginate composite phase change material encapsulated in paraffin of Comparative Example 1. In the figure, PW represents pure paraffin, 5%PW@Ag / HNTA represents the silver / halothite / sodium alginate composite phase change material encapsulated in paraffin of Example 1, and PW@HNTA represents the halloysite / sodium alginate composite phase change material encapsulated in paraffin of Comparative Example 1. As can be seen from the figure, the silver / halothite / sodium alginate composite phase change material encapsulated in paraffin exhibits a significantly enhanced solar energy absorption capacity of approximately 92%. In Comparative Example 1, the light absorption capacity of the halloysite / sodium alginate composite phase change material encapsulated in paraffin obtained in step 5 is not much different from that of pure paraffin, but the light absorption capacity of the halloysite / sodium alginate composite phase change material encapsulated in paraffin is not as good as that of the silver / halothite / sodium alginate composite phase change material encapsulated in paraffin of Example 1.
[0041] The silver / halolite / sodium alginate composite phase change material encapsulated in paraffin, prepared in Examples 1, 2, and 3, was used for hydrogen production via the hydrolysis of ammonia borane. Under illumination, the ammonia borane hydrolyzed to produce hydrogen; the hydrogen production reaction terminated when the light source was turned off. The specific process was as follows: the prepared PW@Ag / HNTA was placed in a three-necked flask, and a certain amount of water was added; subsequently, 1 mL of a 1 M ammonia borane solution was rapidly injected into the flask. The xenon lamp was then alternately turned on and off at 10-minute intervals, and this cycle was repeated 7 times. Hydrogen production was monitored and recorded using the water displacement method. Figure 4 The figure shows a comparison of the hydrogen production performance of silver / halothite / sodium alginate composite phase change materials encapsulated in paraffin prepared in Examples 1, 2, and 3 of this invention under light-on / off conditions; the figures are 5%PW@Ag / HNTA of silver / halothite / sodium alginate composite phase change material with 5% Ag loading prepared in Example 1, 3%PW@Ag / HNTA of silver / halothite / sodium alginate composite phase change material with 3% Ag loading prepared in Example 2, and 1%PW@Ag / HNTA of silver / halothite / sodium alginate composite phase change material with 1% Ag loading prepared in Example 3; it can be seen that the hydrogen production rate increases with the increase of Ag loading in each light-on / off cycle.
[0042] The metal M / halolite / sodium alginate composite phase change material encapsulated in paraffin, prepared in Examples 1, 4, and 5, was used for hydrogen production via the hydrolysis of ammonia borane. Under illumination, the ammonia borane hydrolyzed to produce hydrogen; the hydrogen production reaction terminated when the light source was turned off. The specific process was as follows: the prepared PW@M / HNTA was placed in a three-necked flask, and a certain amount of water was added; subsequently, 1 mL of a 1 M ammonia borane solution was rapidly injected into the flask. The xenon lamp was then alternately turned on and off at 10-minute intervals, and this cycle was repeated 7 times. Hydrogen production was monitored and recorded using the water displacement method.
[0043] like Figure 5 The figure shows a comparison of the hydrogen production performance of halloysite / sodium alginate composite phase change materials with different metal loads on encapsulated paraffin prepared in Examples 1, 4, and 5 of this invention under light-on / off conditions; the figures are: 5%PW@Ag / HNTA silver / haloysite / sodium alginate composite phase change material with 5% Ag loading prepared in Example 1; 5%PW@Ru / HNTA ruthenium / haloysite / sodium alginate composite phase change material with 5% Ru loading prepared in Example 4; and 5%PW@Co / Co / HNTA cobalt / haloysite / sodium alginate composite phase change material with 5% Co loading prepared in Example 5. It can be seen that the hydrogen production performance of the Ru-loaded material is superior to that of the Co and Ag-loaded materials.
[0044] The technical solutions of the present invention are not limited to the specific embodiments described above. Any technical modifications made in accordance with the technical solutions of the present invention fall within the protection scope of the present invention.
Claims
1. A photo-controlled composite phase change material catalyst, characterized in that: The photo-controlled composite phase change material catalyst is a metal M / haloite / sodium alginate composite phase change material encapsulating paraffin; the metal M / haloite / sodium alginate composite phase change material encapsulating paraffin uses halloysite / sodium alginate aerogel supported by metal M nanoparticles as a support material and encapsulates paraffin.
2. The photo-controlled composite phase change material catalyst according to claim 1, characterized in that: The metal M is one of silver, cobalt, and ruthenium.
3. A method for preparing the photocontrolled composite phase change material catalyst according to any one of claims 1 or 2, characterized in that, Includes the following steps: S1, Halloysite nanotubes are added to hydrochloric acid solution and stirred. After stirring, they are washed and dried to obtain acid-treated halloysite nanotubes. S2, acid-treated halloysite nanotubes were added to sodium alginate solution and stirred, glutaraldehyde solution was added and stirred, and then freeze-dried to obtain halloysite / sodium alginate aerogel. S3, Halloysite / sodium alginate aerogel is immersed in a salt solution of metal M, sodium borohydride is added after impregnation, and then freeze-drying is performed to obtain metal M / haloysite / sodium alginate aerogel. S4. The metal M / haloysite / sodium alginate aerogel is immersed in molten paraffin wax to encapsulate the paraffin wax, thereby obtaining a metal M / haloysite / sodium alginate composite phase change material encapsulated in paraffin wax.
4. The method for preparing a light-controlled composite phase change material catalyst according to claim 3, characterized in that: In step S1, the stirring time is 3 hours and the stirring temperature is 80°C; the concentration of the hydrochloric acid solution is 4 mol / L.
5. The method for preparing a light-controlled composite phase change material catalyst according to claim 3, characterized in that: In step S2, the mass fraction of sodium alginate solution is 2%; the mass ratio of acid-treated halloysite nanotubes to sodium alginate in sodium alginate solution is 5:1; the mass-volume ratio of acid-treated halloysite nanotubes to glutaraldehyde solution is 1:1000, with the comparison unit being g: μL; and the mass fraction of glutaraldehyde in glutaraldehyde solution is 25%.
6. The method for preparing a light-controlled composite phase change material catalyst according to claim 3, characterized in that: In step S3, the concentration of the salt solution of metal M is 3 g / L; the mass-to-volume ratio of the acid-treated halloysite nanotubes to the salt solution of metal M is 1:(2-39), and the unit of comparison is g:mL; the mass ratio of the acid-treated halloysite nanotubes to sodium borohydride is 25:
1.
7. The method for preparing a light-controlled composite phase change material catalyst according to claim 3, characterized in that: The salt solution of metal M is one of silver nitrate solution, anhydrous ruthenium chloride solution, or cobalt chloride hexahydrate solution.
8. The method for preparing a light-controlled composite phase change material catalyst according to claim 3, characterized in that: The loading of metal M is 1%-5% of the mass of metal M / haloysite / sodium alginate aerogel.
9. The method for preparing a light-controlled composite phase change material catalyst according to claim 3, characterized in that: In step S5, the encapsulation process of paraffin is automatic encapsulation, and the encapsulation amount of paraffin in the metal M / haloysite / sodium alginate composite phase change material for encapsulating paraffin is 65%-85%.
10. The application of the photocontrolled composite phase change material catalyst according to claim 1 or 2 or the photocontrolled composite phase change material catalyst prepared by any one of claims 3-9 in the hydrolysis of ammonia borane to produce hydrogen.
Citation Information
Cited By
Hormone therapy for breast cancer
CN122465562A